Preliminary Evaluation on AntiFungal Properties of Red Leaf Extract of Syzygium campanulatum - Goh, Jet Yue (2018)
There's a need for more effective antifungals and one of the ways of obtaining them is to test natural flora for their potential antifungal capability. The family Syzygium of plants have long been associated to contain many bioactive compounds including antifungals. In this study, we aimed to obtain Syzygium companalatum (SC) crude leaf extract through ethonal macreation, to separate SC rude leaf extract into the respective fractions and to test antifungal affect of both SC crude leaf extract and fractions against the growth Aspergillus brasiliensis (AB) suspension. The extraction of SC crude extract was performed with athanol maceration for 24 hours and obtained 45% yield of crude extract. An amberlite column chromotography was performed on SC crude extract with three solvent systems, namely methanol (MeOH), ethylacetate (EA) and (MeOH:EA). MeOH.EA and EA solvent systems seprated fractions with the absorbance that have similar absorbance peaks with tested chalcone standard fractions which were fraction-15 and fraction-24 which indicated high possibility of both fractions containing chalcone compound. Based on chalcone standard curve, the chalcone concentrations in both fraction-15 and fraction-24 have 0.011 mg/mL of chaclone. Antifungal assays measured at 620 nm (A620) involving AB suspensions treated for both SC crude extract and fractions through microdilution method. 20uL to 100 uL of crude extract have antifungul inhinition against AB growth within 24 hours. Whereas all three SC fractions treatment did not achieve antifungul inhibitory effect due to low chalcone concentration. In conclusion, chalcone was successfully isolated from SC crude extract through column chromatography and antifungal assay of AB treated with crude extract was tested positive for inhibition